Outline of a Darwinian theory of money - Carsten Herrmann-Pillath (Frankfurt School of Finance & Management, 2009)
Building on Lea and Webley's drug theory of money, the paper connects different theoretical resources to develop a Darwinian theory of money. The central empirical observation is the neuroeconomic result of the independent role of money as a reinforcer, which matches with a series of other insights into strong emotional impact of money use. Lea and Webley proposed that money piggybacks on a generalized instinct for social exchange. I put this into the more universal framework of the Darwinian concept of signal selection and Aunger's theory of neuromemes. This can be related to Searle's theory of institutions, especially with regard to his notion of neurophysiological dispositions as a basis for rule-following. Thus, neuroeconomics and institutional theory can be put into one coherent framework of Generalized Darwinism, taking money and its emergence as a case study.
urn:nbn:de:101:1-20090923136
Keywords: B52; D03; D58; E40; 330; Money emotions; Searle's theory of institutions; conceptual blending; emergence of money; neuronal Darwinism